Access and local government research: Methodological reflections - Pini, B.; McKenzie, Fiona Haslam (Taylor & Francis, 2007)
This methodological paper draws on research from Australia to examine the question of gaining access to local governments in undertaking work on natural resource management. It is argued that a range of macro-level changes have impacted on the local government sector in Australia, and these changes have rendered access problematic for researchers. These changes include an expansion of local government roles, an increase in financial pressure within the sector, a proliferation of audit measures across local governments and a low level of respect amongst local government personnel for academics and academic work. The paper concludes by identifying the reasons why understanding access in qualitative research on local government and environmental sustainability is important.